The development of a probing prompting-based student worksheet to improve fourth grade students’ critical thinking ability - Putri Permatasari; Pramudiyanti Pramudiyanti; Alben Ambarita; Lilik Sabdanintyas (Lighthouse Publishing, 2022)
This study aims to develop a probing prompting-based student worksheet to improve students' critical thinking skills. The research followed the Borg & Gall research and development model, conducted at SD Negeri 1 Metro Timur, Metro City, Lampung, Indonesia. This research adopted a purposive sampling technique with a total of 46 students divided into 23 students in the experimental class and 23 students in the control class. The research data collection techniques were obtained using questionnaires, documentation, and learning outcomes tests. The results showed that the probing prompting-based student worksheet developed was feasible, interesting, easy, useful and effective to use. Finally, the findings have implications and limitations for future research.